Metodología de enseñanza de la lectura para la comprensión de textos en inglés a estudiantes del primer año de bachillerato general unificado, paralelo a de la Unidad Educativa Zoila Ugarte de Landívar del cantón Santa Rosa, provincia El Oro, año 2013 - Martínez Delgado, Ana Marlene (2013)
Having a quality education in all schools is the current challenge of the government and therefore the challenge of all teachers, that is why this research assumes an integrative conceptualization of learning in general, the particular language and reading and understanding as a universal process, directed to favor the formation of the student since a moderate position as a teacher of English, in which is considered the importance of reading in the teaching-learning process, since students must extract meaning from written texts to express their ideas, opinions and draw their own conclusions.